Hematological Alterations in the Fish Channastriata Exposed to Heavy Metal Pollution from River Kharun, Chhattisgarh (India) - Chiranjeev Pandey,; Alka Mishra,; Akhilesh Kumar,; Ewraj Janghel,; Majid Ali,; Neelesh Kumar Dhalendra, (The Bioscan, 2026)
The present study investigates the impact of heavy metal contamination on the hematological parameters of the freshwater fish Channastriata (Bloch), a widely distributed and ecologically significant and tolerant species. Water samples were collected seasonally from 03 selected sites of the Kharun River, and the concentrations of major heavy metals (such as Iron, cadmium, lead, nickel, and mercury) were analyzed. Corresponding fish specimens were examined for blood parameters, including hemoglobin content, red blood cell (RBC) count, white blood cell (WBC) count, PCV,MCV& MCHC values. The results revealed significant alterations in these parameters, indicating physiological stress and potential immunosuppression. Decreased hemoglobin levels and RBC counts, along with increased WBC counts, suggest anemia and inflammatory responses in the exposed fish. This study highlights the bio-indicative role of Channastriata in freshwater ecosystems and underscores the need for continuous monitoring of heavy metal contamination in freshwater ecosystems.